PENGARUH EKSTRAK ETIL ASETAT GETAH KAMBOJA (Plumeria Acumenate.W.T.Ait) TERHADAP PERTUMBUHAN DAN DAYA HAMBAT BAKTERI Staphylococus aureus - R. T. Wahyudi; Sukarjati sukarjati (FMIPA : Universitas PGRI Adi Buana, 2013)
Frangipani sap (Plumeria acumenate.WTAit) was known to use as an antiseptic. This study aimed to prove ethyl acetate extract of frangipani sap as antibacterial Staphylococcus aureus. Frangipani sap from apical stem was extracted with chloroform and fractionated with ethyl acetate. Concentration of ethyl acetate extract (0%, 5%, 10%, 15%, 20%, and 25%) were tested against the growth of bacteria S. aureus using plate count and diffusion agar method. The results showed concentrations of frangipani sap extract significantly (P <0.05) on the growth of S. aureus. Highest inhibitions of frangipani sap extract on growth of S. aureus have obtained at a concentration of 25%. Key words: frangipani sap, ethyl acetate, S. aureus